1981
DOI: 10.1111/j.1651-2227.1981.tb06239.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ceroidlipofuscinosis: CCT Findings in Fourteen Patients

Abstract: CCT was performed in 14 children/adolescents with juvenile ceroid lipofuscinosis (JNCL) at different stages of the disease. CCT was normal in 7 patients; mildly abnormal in 3, clearly abnormal in another 3 and severely abnormal in 1 patient. Characteristic findings were symmetrical enlargement of subarachnoid spaces and of the lateral and third ventricles. White matter showed no changes in density. In later stages also the fourth ventricle was enlarged and cerebellar atrophy was seen. CCT findings were not clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The CT findings in JNCL are unspecific, but they correlate with the severity of the disease. A positive correlation with age was found, just as in earlier studies (8,9). Positive correlations were also found between cerebellqr disease and motor functions as weIl as ADL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The CT findings in JNCL are unspecific, but they correlate with the severity of the disease. A positive correlation with age was found, just as in earlier studies (8,9). Positive correlations were also found between cerebellqr disease and motor functions as weIl as ADL.…”
Section: Discussionsupporting
confidence: 88%
“…We studied 32 patients with CT. Previously, CT findings have been described in 20 patients (8,9). All patients under the age of 9 have been radiologically normal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A previously published CT study also showed increased subarachnoid and ventricular spaces, which were correlated with patient age. 16 However, CT findings were usually normal in patients younger than 10 years of age, and these findings did not correlate with onset or severity of the abnormalities, possibly reflecting the diverse forms of neuronal ceroid lipofuscinosis in this study before genetic testing. 16 MR spectroscopic imaging (MRSI) has also been used to noninvasively assess brain metabolism in various neurodegenerative diseases, such as Alzheimer and Parkinson diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Conventional MR imaging and CT have been used to demonstrate the presence of cerebral atrophy in multiple forms of neuronal ceroid lipofuscinosis. [13][14][15][16] However, atrophic grading using conventional MR imaging is only a subjective measure of disease severity. A diffuse hyperintensity of cerebral white matter has been reported in LINCL patients.…”
Section: Discussionmentioning
confidence: 99%